PENGUATAN DAYA SAING LEMBAGA PENDIDIKAN ISLAM MELALUI OPTIMALISASI DIGITAL ADVERTISING DALAM REKRUTMEN PESERTA DIDIK BARU - Muhammad Kamil; Febi Febrianto; Uryatul Hikmah; Muthia Hasanah; M. Kholilur Rohman; Akmal Mundiri (CV Narasi Khatulistiwa Indonesia, 2026)
This study aims to analyze the strategy of optimizing digital advertising in strengthening the competitiveness of Islamic educational institutions through increasing the effectiveness of new student recruitment. The research uses a qualitative approach with a case study method on Islamic educational institutions that actively use digital media as a means of promotion. Data was obtained through observation, interviews, documentation, and literature studies, then analyzed using data reduction techniques, data presentation, and conclusion drawn. The results of the study show that the use of digital advertising through social media, websites, and digital advertising platforms is able to increase the visibility of institutions, expand the reach of information, build a positive image, and increase interaction with prospective students and parents. Effective strategies include presenting informative and engaging content, using professional visual design, and utilizing segmented paid advertising features. The implementation of this strategy has proven to support the increase in the number of registrants and strengthen the competitive position of Islamic educational institutions in the midst of increasingly fierce competition. The implications of this research emphasize the importance of strengthening the digital capacity of Islamic educational institutions and the development of technology-based marketing strategies as a sustainable effort to increase the competitiveness and sustainability of educational institutions in the digital era.